2005
DOI: 10.1002/bjs.4823
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal complications after cardiac surgery

Abstract: Nine risk factors for the development of major gastrointestinal complications after cardiac surgery were identified. Gastrointestinal complications were often lethal but did not independently predict death within 30 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 25 publications
8
61
2
4
Order By: Relevance
“…[1][2][3][4][5][6][7][8] In our study, the incidence of GI complications in patients undergoing mitral valve surgery was 2.3% with a 30-day mortality of 39%, both of which consistent with existing reports. Valvular surgery was suggested to correlate with higher incidence of GI complications both by univariate [9][10][11][12][13] and multivariate 3,14) analysis, and our incidence is in agreement with this observation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] In our study, the incidence of GI complications in patients undergoing mitral valve surgery was 2.3% with a 30-day mortality of 39%, both of which consistent with existing reports. Valvular surgery was suggested to correlate with higher incidence of GI complications both by univariate [9][10][11][12][13] and multivariate 3,14) analysis, and our incidence is in agreement with this observation.…”
Section: Discussionsupporting
confidence: 90%
“…However, mortality in these patients is high, ranging from 11%-70% in various studies. [1][2][3][4][5][6][7][8] Multiple published reports have examined GI complications after cardiac surgery in general. This represents a heterogeneous group of pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent international cohort study showed that preexisting liver disease, need for RRT, and higher organ failure scores were independent predictors of GI bleeding risk [533]. A multicenter prospective cohort study found the incidence of clinically important GI bleeding to be 2.6% (95% CI 1.6-3.6%) in critically ill patients [533]; however, other observational studies showed lower rates of GI bleeding [534][535][536][537].…”
Section: S Stress Ulcer Prophylaxismentioning
confidence: 99%
“…Incidence and frequency Abdominal complications after CPB for cardiac surgery are seen in < 1% of patients [124][125][126][127][128][129][130][131][132] but carry a high mortality of 14.1% [131] . AMI represents 10%-67% of these complications [129,133,134] , and is the most lethal, with a case-fatality rate of 70% to 100% [129,131,132,135,136] .…”
Section: Ami After Cpbmentioning
confidence: 99%